Using neural networks to locate pitch accents. - Taylor, Paul A (International Speech Communication Association, 1995)
This paper descirbes a technique for finding intonatioanl events, (pitch accents and boundary tones) from waveforms. The technique works in a bottom-up manner by using a recurrent neural network to perform a classification of each frame in the input waveform. An autosegmental description, consisting of intonational events, syllables and the links between them, is then produced from this frame-based classification. The technique correctly identifies 85.7% of pitch accents and boundary tones.